Challenges to informed consent for exome sequencing: A best–worst scaling experiment. Issue 6 (25th September 2019) - Gore, Rachel H.; Bridges, John F. P.; Cohen, Julie S.; Biesecker, Barbara B.
Abstract: As exome sequencing expands as a diagnostic tool, patients and providers have voiced concerns about communicating the breadth and scope of potential results when obtaining informed consent. This study aimed to understand how genetic counselors prioritize essential components of the informed consent process and whether counselor factors influence these decisions. Development of a best–worst scaling experiment was informed by a systematic literature review and two focus groups. In all, 11 choice sets were created using a balanced incomplete block design, where participants selected the most and least important object in each set. Mean best–worst (BW) scores were calculated to summarize the relative importance of each object, and mediation analyses assessed whether responses were associated with genetic counselor factors and attitudes. In all, 342 members of the National Society of Genetic Counselors completed the online survey. Ranking of BW scores suggests that participants prioritize collaborative decision‐making, assessing understanding and managing expectations, with the least emphasis placed on discussing technological complexities. Stratified analyses found that counselors more experienced with obtaining informed consent for exome sequencing and those reporting higher perceptions of patients' ability to manage information rated discussing variants of uncertain significance as significantly more important ( p  < .05). Our results suggest that genetic counselors report intentions to prioritize individual patient needs when obtaining informed consent for exome sequencing. Professional characteristics and attitudes may influence preemptive discussion of uncertain results.